2011
DOI: 10.1603/ec11064
|View full text |Cite
|
Sign up to set email alerts
|

Host Suitability and Gas Exchange Response of Grapevines to Potato Leafhopper (Hemiptera: Cicadellidae)

Abstract: Although potato leafhopper, Empoasca fabae (Harris) (Hemiptera: Cicadellidae), is highly polyphagous, classic host studies do not recognize grapevines (Vitis spp.), as suitable hosts. Recently, injury has been reported and reproduction documented within grape vineyards, suggesting a host expansion for the leafhopper. To document this apparent expansion in host use, we determined whether grape plants were suitable hosts for potato leafhopper reproduction, measured the consequence of feeding injury on gas exchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
2
1
0
Order By: Relevance
“…Our results also contribute to the increasing recognition of grapevine as a host plant for other leafhopper species than E. vitis (Mazzoni et al. 2001; Tiefenbrunner and Tiefenbrunner 2007; Lamp et al. 2011).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Our results also contribute to the increasing recognition of grapevine as a host plant for other leafhopper species than E. vitis (Mazzoni et al. 2001; Tiefenbrunner and Tiefenbrunner 2007; Lamp et al. 2011).…”
Section: Discussionsupporting
confidence: 56%
“…Reineke and M. Hauck therefore have a certain potential to also cause damage to grapevine plants. Our results also contribute to the increasing recognition of grapevine as a host plant for other leafhopper species than E. vitis (Mazzoni et al 2001;Tiefenbrunner and Tiefenbrunner 2007;Lamp et al 2011).…”
Section: Development Of Leafhopper Larvae On Grapevinesupporting
confidence: 56%
“…Insect phloem feeding can either promote or reduce C assimilation in host plants (Zhou et al, 2015 ). Evidence of reductions in grapevine C assimilation by phloem‐feeding insects has mostly involved insects that directly feed upon leaf tissues (Candolfi et al, 1993 ; Lamp et al, 2011 ; Lenz et al, 2012 ) or form galls (Nabity et al, 2013 ). In this study, we showed that prolonged exposure to SLF, an insect that feeds on the phloem of stems and trunks, can decrease photosynthetic rate, similar to other sap‐feeding insect pests of woody (Zvereva et al, 2010 ) and herbaceous plants (Watanabe & Kitagawa, 2000 ).…”
Section: Discussionmentioning
confidence: 99%